2016
DOI: 10.2174/1574888x11666160614102629
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stromal-Derived Factor-1 in Mesenchymal Stem Cell Paracrinemediated Tissue Repair

Abstract: In addition to the multi-lineage differentiation potential of mesenchymal stem cells (MSCs), studies in recent years have focused on the role of MSC paracrine in tissue regeneration. Due to their paracrine effects in damaged tissues, MSCs may be a promising therapeutic cell type in the treatment of many disorders. However, the mechanisms underlying the effects of MSC paracrine on tissue regeneration remain largely unknown, which limits the development of therapeutic applications. Stromalderived factor-1 (SDF-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…6 ). High-density cell injection at the topical region is also an obstacle for homing, thus using a vasodilator like heparin, culturing the cells under hypoxic condition, maintaining a lower confluence, or the addition of IL-3, IL-6, IGF-1, tumor necrosis factor alpha (TNF-α), or interferon-gamma (IFN-γ), can be used to increase C-X-C chemokine receptor type 4 (CXCR-4) [ 38 ], which is a specific receptor for stromal-derived-factor-1 (SDF-1, also called CXCL12), an MSC chemotactic factor that could improve homing efficiency [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…6 ). High-density cell injection at the topical region is also an obstacle for homing, thus using a vasodilator like heparin, culturing the cells under hypoxic condition, maintaining a lower confluence, or the addition of IL-3, IL-6, IGF-1, tumor necrosis factor alpha (TNF-α), or interferon-gamma (IFN-γ), can be used to increase C-X-C chemokine receptor type 4 (CXCR-4) [ 38 ], which is a specific receptor for stromal-derived-factor-1 (SDF-1, also called CXCL12), an MSC chemotactic factor that could improve homing efficiency [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…TSG-6 has anti-inflammatory action and, furthermore, a specific inhibitory function against MMPs [ 30 ]. Finally, SDF-1 and its receptor are key players in the recruitment of MSCs and endothelial cells in inflamed, as well as in damaged tissues [ 31 , 32 ]. Equine aMSCs express STC-1, IL1-Ra, TSG-6, and SDF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the potential role of MSCs in various biological processes like contributing to cell generation, survival, and alteration of cellular phenotype [27][28][29] . MSCs govern the repair mechanisms occurring at cellular and molecular levels by communication through the release of different factors mostly proteins 30 . In this study, we investigated the potential role of MSCs in the repair of the plasma membrane and chromatin material of dog sperm following cryopreservation.…”
Section: Discussionmentioning
confidence: 99%